2023
DOI: 10.21062/mft.2023.085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Corrosion Resistance of the Al-Si-Cu-Mg Alloy with the Addition of Zirconium

Marek Matejka,
Dana Bolibruchová,
Daniel Kajánek

Abstract: Aluminum alloys are one of the most used materials today, and therefore great emphasis is placed on their continuous development. Improving the ratio of strength and stiffness to weight, improving plasticity, casting properties or resistance to corrosion are examples of properties of aluminum alloys that are constantly being improved. This work focuses on the evaluation of the corrosion resistance of the Al-Si5Cu2Mg alloy with graded addition of zirconium (0.05; 0.10; 0.15; 0.20 wt.%). Corrosion resistance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…To address these limitations, M. Matejka’s research group suggested the corrosion rate of Al-Si5Cu2-Mg alloy according to Zr content and showed the corrosion resistance was improved if 0.1 wt% Zr was added [ 4 ]. P, Zhou et al reported that the addition of Cr to Al-Si-Cu-Mg alloy not only improves corrosion resistance but also mechanical properties [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address these limitations, M. Matejka’s research group suggested the corrosion rate of Al-Si5Cu2-Mg alloy according to Zr content and showed the corrosion resistance was improved if 0.1 wt% Zr was added [ 4 ]. P, Zhou et al reported that the addition of Cr to Al-Si-Cu-Mg alloy not only improves corrosion resistance but also mechanical properties [ 5 ].…”
Section: Introductionmentioning
confidence: 99%